PROBLEMS OF OPERATION OF TRUCKS IN THE REGIONS OF KAZAKHSTAN - Zhumatayeva G.,; Bitileuova Z.,; Baiburaeva Zh.,; Zhanbirov Zh.,; Taran I., (Scientific Journal of Pedagogy and Economics, 2020)
Improving the efficiency of the transport system will make it a competitive element of the Kazakh economy. Will be achieved the highest level of security needs of the economy and population in a safe and secure transportation services. This research work, according to the current economic policy of the Republic, taking into account the specific conditions of development, aimed at improving the efficiency of trucks on the basis of theory and methods of transportation logistics and management in accordance with the level of a modern transport system.